Yawning in Depression: Worth Looking Into - Hensch, T.; Blume, A.; Böttger, D.; Sander, C.; Niedermeier, N.; Hegerl, U. (Pharmacopsychiatry, 2015)
Yawning often occurs during states of increased sleep propensity. Depression is associated with sleep problems and tiredness. The aim of this paper is to review the present knowledge about possible changes of yawning during an episode of major depression (MD) and to report data on yawning from an online depression forum comprising of 450 000 postings. A literature search did not reveal any study about yawning in people with MD when compared to controls. However, there is evidence for an increased frequency of yawning under the influence of antidepressants. Analysis of the depression forum postings revealed 63 people writing about increased yawning in the context of depression. However, all but one of them were treated with antidepressants; and yawning was not reported as a symptom of depression, but in most cases (N=56) as occurring as a result of treatment with antidepressants. These findings are in agreement with a tonic hyperarousal in typical depression which is reduced by all standard antidepressants. For clinicians, it would be of interest to know whether yawning is reduced in untreated depression and whether it predicts treatment outcome.
Keywords: yawning; depression; vigilance; sleepiness; antidepressants